Penyuluhan Stase Komunitas Mengenai Sikap Ergonomis untuk Mengurangi Terjadinya Musculoskeletal Disorders di Komunitas PKK Desa Genengan Pakisaji Kabupaten Malang - Fachry Raul Aimar Zinedine El Addin; Ali Multazam; Qonitatul Fitriyah (Health Care : Journal of Community Service, 2025)
Introduction: Health is an important element so that we can enjoy a quality life, both at home and at work. Musculoskeletal disorders are diseases that cause prolonged pain. A person who suffers from musculoskeletal disorders occurs due to a body position while working that is less ergonomic and occurs for a long time and repeatedly. Basically, ergonomic conditions are very beneficial because the prevent musculoskeletal disorders and can reduce errors that can cause injury to workers. Purpose: Provide an overview of how to behave ergonomically when doing work to avoid musculoskeletal disorders. Method: Provide counseling on the definition, causes, how to handle, and how to train for workers using posters as a promotional media. Conclusion: The counseling process went smoothly, respondents began to understand ergonomic positions and musculoskeletal disorders with the aim of getting workers' understanding from 0% to 100% after the counseling was carried out. So that there is a decrease in the risk of musculoskeletal disorders experienced by workers after knowing the ergonomic attitude. The counseling activities that have been carried out at the Genengan Village Hall, Malang Regency, can increase workers' knowledge and insight regarding ergonomic attitudes and musculoskeletal disorders.